2020
DOI: 10.1038/s41467-020-16565-2
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the boundaries of optoacoustic microscopy by total impulse response characterization

Abstract: Optical microscopy improves in resolution and signal-to-noise ratio by correcting for the system's point spread function; a measure of how a point source is resolved, typically determined by imaging nanospheres. Optical-resolution optoacoustic (photoacoustic) microscopy could be similarly corrected, especially to account for the spatially-dependent signal distortions induced by the acoustic detection and the time-resolved and bi-polar nature of optoacoustic signals. Correction algorithms must therefore include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…We next tested the optical and OA characteristics of C 70 @lysozyme to investigate its potential as a contrast agent for phototheranostics. Using a custom‐built hybrid microscopy system, [ 68–73 ] which combines optical‐resolution OA, THG, and 2PEF microscopy, we clearly demonstrated that C 70 generates significant THG response (Figure S9A, Supporting Information) as well as intense OA signal (Figure S9B, Section S9, Supporting Information) when dispersed on a microscope slide.…”
Section: Resultsmentioning
confidence: 99%
“…We next tested the optical and OA characteristics of C 70 @lysozyme to investigate its potential as a contrast agent for phototheranostics. Using a custom‐built hybrid microscopy system, [ 68–73 ] which combines optical‐resolution OA, THG, and 2PEF microscopy, we clearly demonstrated that C 70 generates significant THG response (Figure S9A, Supporting Information) as well as intense OA signal (Figure S9B, Section S9, Supporting Information) when dispersed on a microscope slide.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, K laser refers to the laser-induced spatially dependent convolution kernel corresponding to the spot size, signal reception time, and thermal effects. Moreover, K electric is the convolution kernel corresponding to an ultrasonic sensor that is spatially dependent [21,22]. N 1 is the noise produced by the interaction between laser and matter, and N 2 is the noise caused by ultrasonic sensors.…”
Section: Mems-based Or-pammentioning
confidence: 99%
“…This compensation was achieved by experimentally measuring the spatial transfer function and applying it as a multiplicative weighting function in the frequency domain inversion scheme of the acquired RSOM data. Although incorporating the PSF has been shown to successfully improve the quality of reconstructed optoacoustic images 30,46,47 and detector sensitivity fields have been included in reconstruction algorithms to account for negatively focused ultrasound transducers 48,49 , these studies were performed in the time-domain and suffered from long processing times. Here we incorporate the PSF correction factor in the reconstruction problem in the Fourier domain to avoid sacrificing computational time.…”
Section: Discussionmentioning
confidence: 99%